Revision der von Ferdinand Rudow beschriebenen Ichneumonidae I. (Hymenoptera). - Horstmann, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1993)
Ferdinand Rudow (1840-1920) described 234 species and varieties in the family Ichneumonidae (Hymenoptera), 167 of which are revised here (all except those described in the genera Pezolochus Förster and Pezomachus Gravenhorst). Nearly all of these taxa come from the Western Palaearctic Region, but one taxon is Nearctic (Ophion undulatus Gravenhorst var. giganteus) and another Neotropic (Crypturus gracilis). The types of 115 taxa were found in Rudow’s collection in the Phyletic Museum in Jena, and for 92 taxa the lectotypes are designated. Two of these taxa turned out to belong to the Braconidae and Scelionidae, respectively (Aptesis macroptera, Aptesis unicolor). In six cases the types could not be identified with other described species. Of the 52 taxa not represented by types, 28 could be identified by help of other means (references in literature, Rudow’s descriptions, non-types present in the collection), and 24 taxa remain nomina dubia. All in all 119 new synonyms are indicated. In 128 cases Rudow’s species-group names were found to be junior synonyms and/or homonyms, whereas at present only 11 species-group names given by Rudow are considered to be valid names for known species or subspecies. A number of peculiarities of Rudow’s work and collection are pointed out. Nomenclatural Acts ephippium Rudow, 1914 (Agrothereutes), Lectotype; syn. n. of Aptesis nigrocincta (Gravenhorst, 1815) fulvipes Rudow, 1914 (Agrothereutes), Lectotype; syn. n. of Aptesis nigrocincta (Gravenhorst, 1815) rufiventris Rudow, 1917 (Agrothereutes), Lectotype; syn. n. of Theroscopus bonelli (Gravenhorst, 1815) aetnensis (Rudow, 1883) (Allophatnus), Lectotype described as Cryptus aetnensis bellemitus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Ichneumon steckii Kriechbaumer, 1887 bicolor Rudow, 1888 (Amblyteles), Lectotype; syn. n. praeocc. from A. bicolor Kriechbaumer, 1882; syn. of Ctenichneumon repentinus (Gravenhorst, 1820) bipunctatus Rudow, 1888 (Amblyteles), syn. n. of Diphyus quadripunctorius (Müller, 1776) bizonatus Rudow, 1888 (Amblyteles), syn. n. of Ichneumon lautatorius Desvignes, 1856 croceiventris Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Ichneumon molitorius Linnaeus, 1761 diversipes Berthoumieu, 1897 (Amblyteles), syn. n. of Triptognathus fumipennis (Rudow, 1888) dromedarius Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Coelichneumon rudis (Boyer de Fonscolombe, 1847) erythropygus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Ctenichneumon melanocastanus (Gravenhorst, 1829) fumipennis Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Pseudoamblyteles homocerus (Wesmael, 1854) gynandromorphus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Ichneumon melanobatus Gravenhorst, 1829 italicus Rudow, 1888 (Amblyteles), syn. n. of Protichneumon fusorius (Linnaeus, 1761) laticeps Rudow, 1888 (Amblyteles), syn. n. of Coelichneumon serenus (Gravenhorst, 1820) laticinctus Rudow, 1888 (Amblyteles), syn. n. of Eutanyacra crispatoria (Linnaeus, 1758) lotharingicus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Ctenichneumon edictorius (Linnaeus, 1758) muticus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Ichneumon luteipes Wesmael, 1855 palliventris Rudow, 1888 (Amblyteles), syn. n. of Hepiopelmus melanogaster (Gmelin, 1790) quadrimaculatus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Triptognathus fumigator (Gravenhorst, 1820) ruficornis Rudow, 1888 (Amblyteles), syn. n. of Ichneumon inops Holmgren, 1880 rufipes Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Coelichneumon rudis (Boyer de Fonscolombe, 1847) severus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Triptognathus fumigator (Gravenhorst, 1820) siculus Rudow, 1888 (Amblyteles), syn. n. of Eutanyacra glaucatoria (Fabricius, 1793) sulfureopictus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Ichneumon inquinatus Wesmael, 1844 tristis Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Triptognathus rubricinctus (Lucas, 1849) violaceus Rudow, 1888 (Amblyteles), Lectotype; syn. n. of Hoplismenus lamprolabus Wesmael, 1857 zonatus Rudow, 1888 (Amblyteles), syn. n. of Triptognathus unifasciatus (Spinola, 1843) alpina Rudow, 1917 (Aptesis), Lectotype; syn. n. of Pleolophus vestigialis (Förster, 1850) borealis Rudow, 1917 (Aptesis), Lectotype; syn. n. of Aptesis nigrocincta (Gravenhorst, 1815) livonensis Rudow, 1917 (Aptesis), Lectotype; syn. n. of Agrothereutes abbreviatus (Fabricius, 1794) macroptera Rudow, 1917 (Aptesis), Lectotype; syn. n. of Orgilus parvipennis Thomson, 1895 spectabilis Rudow, 1886 (Aptesis), Lectotype; syn. n. of Agrothereutes abbreviatus (Fabricius, 1794) tricolor Rudow, 1886 (Aptesis), syn. n. of Agrothereutes abbreviatus (Fabricius, 1794) unicolor Rudow, 1917 (Aptesis), Lectotype; syn. n. of Trimorus varicorenis (Walker, 1836) crassicornis Rudow, 1886 (Banchopsis), Lectotype collaris (Rudow, 1883) (Caenocryptus rufiventris), Lectotype; stat. n. dedscribed as Cryptus collaris impunctatus Schwarz, 1991 (Caenocryptus rufiventris), syn. n. of Caenocryptus rufiventris collaris (Rudow, 1883) erythronotus (Rudow, 1888) (Coelichneumon), Lectotype described as Amblyteles erythronotus purpurissatus Perkins, 1953 (Coelichneumon), syn. n. of Coelichneumon erythronotus (Rudow, 1888) maximus Rudow, 1881 (Coleocentrus), syn. n. of Coleocentrus caligatus (Gravenhorst, 1829) ruficornis Rudow, 1881 (Coleocentrus), Lectotype; syn. n. of Mesoclistus rufipes (Gravenhorst, 1829) scutellaris Rudow, 1881 (Coleocentrus), Lectotype; syn. n. of Exatastes rufipes (Gmelin, 1790) aculeatus Rudow, 1883 (Cryptus), Lectotype; syn. n. of Listrognathus ligator (Gravenhorst, 1829) annulitarsis Rudow, 1882 (Cryptus), Lectotype; syn. n. of Ischnus alternator (Gravenhorst, 1829) bicolor Rudow, 1882 (Cryptus), syn. n. of Cryptus inculcator (Linnaeus, 1758) crassicornis Rudow, 1883 (Cryptus), Lectotype; syn. n. of Hoplismenus albifrons (Gravenhorst, 1829) dineurae Rudow, 1882 (Cryptus), Lectotype; syn. n. of Ischnus agitator (Olivier, 1792) elongatus Rudow, 1882 (Cryptus), syn. n. of Mesostenus grammicus Gravenhorst, 1829 ephippium Rudow, 1886 (Cryptus), Lectotype; syn. n. of Aoplus ochropis (Gmelin, 1790) erythronotus Rudow, 1882 (Cryptus), Lectotype; syn. n. of Neotypus nobilitator (Gravenhorst, 1807) erythrosoma Rudow, 1882 (Cryptus), Lectotype; syn. n. Cryptus inculcator (Linnaeus, 1758) filicornis Rudow, 1886 (Cryptus), syn. n. of Cryptus armator Fabricius, 1804 flavopictus Rudow, 1883 (Cryptus), Lectotype; syn. n. of Ischnus inquisitorius (Müller, 1776) gallarum Rudow, 1882 (Cryptus), Lectotype; syn. n. of Mesostenus transfuga Gravenhorst, 1829 genuicinctus Rudow, 1886 (Cryptus), syn. n. of Alloplasta piceator (Thunberg, 1822) histrionicus Rudow, 1882 (Cryptus), Lectotype; syn. n. of Cryptus apparitorius (Villers, 1789) humeralis Rudow, 1882 (Cryptus), Lectotype; syn. n. of Aritranis femoralis (Gravenhorst, 1829) hymotomadum Rudow, 1883 (Cryptus), Lectotype, syn. n. of Agrothereutes fumipennis (Gravenhorst, 1829) illustris Rudow, 1882 (Cryptus), syn. n. of Xylophrurus augustus (Dalman, 1823) leucozonius Rudow, 1882 (Cryptus), Lectotype; syn. n. of Synechocryptus mactator (Tschek, 1870) lippensis Rudow, 1883 (Cryptus), Lectotype; syn. n. of Cryptus inculcator (Linnaeus, 1758) longiseta Rudow, 1882 (Cryptus), Lectotype; nom. praeocc. from Cryptus longiseta Taschenberg, 1871 macrophyiae Rudow, 1911 (Cryptus), syn. n. of Aritranis bellosa bellosa (Curtis, 1837) myrmecoleontis Rudow, 1888 (Cryptus), Lectotype; syn. n. of Mymeleonostenus italicus (Gravenhorst, 1829) napiformis Rudow, 1882 (Cryptus), Lectotype, syn. n. of Apsilops aquaticus (Thomson, 1874) pectinitarsis Rudow, 1882 (Cryptus), Lectotype; syn. n. of Meringopus titillator (Linnaeus, 1758) picticornis Rudow, 1882 (Cryptus), Lectotype; syn. n. of Thrybius praedator (Rossi, 1792) poecilopus Rudow, 1883 (Cryptus), Lectotype; syn. n. of Plectocryptus digitatus (Gmelin, 1790) robustus Rudow, 1882 (Cryptus), Lectotype; syn. n. of Listrognathus obnoxius (Gravenhorst, 1829) rufifrons Rudow, 1883 (Cryptus), syn. n. of Chirotica rubrotincta rubrotincta (Thomson, 1885) senilis Rudow, 1882 (Cryptus), Lectotype; syn. n. of Lisgtrognathus ligator (Gravenhorst, 1829) tuberculipes Rudow, 1886 (Cryptus), Lectotype; syn. n. of Meringopus calescens (Gravenhorst, 1829) spectabilis Rudow, 1882 (Ctenopelma), Lectotype; syn. n. of Rhorus punctus (Gravenhorst, 1829) mauritanicus (Rudow, 1888) (Diphyus), Lectotype described as Amblyteles mauritanicus ascaniae Rudow, 1883 (Ephialtes), Lectotype now a synonym of Liotryphon ruficollis (Desvignes, 1856) balanini Rudow, 1883 (Ephialtes), Lectotype now a synonym of Tromatobia oculatoria (Fabricius, 1798) ruficollis Rudow, 1881 (Ephialtes), syn. n. of Paraperithous gnathaulax (Thomson, 1877) ruficornis Rudow, 1883 (Exatastes), syn. n. of Xenoschesis fulvipes (Gravenhorst, 1829) brunniventris Rudow, 1883 (Exochus), Lectotype; syn. n. of Hyperacmus crassicornis (Gravenhorst, 1829) brevicornis Rudow, 1883 (Glypta), Lectotype now a synonym of Glypta consimilis Holmgren, 1860 ephippium Rudow, 1886 (Hemimachus), Lectotype; syn. n. of Gelis areator (Panzer, 1804) gallarum Rudow, 1881 (Hemiteles), Lectotype; syn. n. of Mesostenus transfuga (Gravenhorst, 1829) hellbachi Schmiedeknecht, 1905 (Hemiteles), syn. n. of Sulcariusa bispinosus (Rudow, 1886) maculipennis Rudow, 1886 (Hemiteles), Lectotype; syn. n. of Orthizema subannulatum (Bridgman, 1883) microgastri Rudow, 1886 (Hemiteles), syn. n. of Gelis areator (Panzer, 1804) nebulosus Rudow, 1886 (Hemiteles), Lectotype; syn. n. of Gnotus tenuipes (Gravenhorst, 1829) pectoralis Rudow, 1886 (Hemiteles), Lectotype; syn. n. of Megastylus cruentator Schioedte, 1838 ruficollis Rudow, 1886 (Hemiteles), Lectotype; syn. n. of Gelis areator (Panzer, 1804) sericeus Rudow, 1886 (Hemiteles), Lectotype; syn. n. of Gelis areator (Panzer, 1804) ichneumonoides Rudow, 1883 (Hoplismenus bidentatus var.), stat. n.; syn. n. described as Cryptus ichneumonoides cruentata (Rudow, 1883) (Itoplectis maculator), Lectotype; stat. n. described as Pimpla cruentata normannica Rudow, 1883 (Limneria), Lectotype; syn. n. of Diadegma crassicorne (Gravenhorst, 1829) spectabilis Rudow, 1883 (Limneria), Lectotype, syn. n. of Sinophorus turionus (Ratzeburg, 1844) fumipennis Rudow, 1881 (Meniscus), Lectotype; syn. n. of Lissonota conflagrata Gravenhorst, 1829 minutus Rudow, 1881 (Meniscus), Lectotype; syn. n. of Otlophorus pulverulentus (Holmgren, 1857) agriolus Rudow, 1882 (Mesostenus), syn. n. of Picardiella melanoleuca (Gravenhorst, 1829) hellenicus Schmiedeknecht, 1905 (Mesostenus), syn. n. of Allophatnus aetnensis (Rudow, 1883) ruficollis Rudow, 1882 (Mesostenus), syn. n. of Stenarella domator cruentator (Klug, 1835) variegatum Rudow, 1883 (Ophion), syn. n. of Ophion obscuratus Fabricius, 1798 giganteus Rudow, 1883 (Ophion undulatus var.), syn. n. of Enicospilus americanus (Christ, 1791) separatus Schmiedeknecht, 1906 (Pezomachus), syn. n. of Gelis atrata (Rudow, 1886) brumatae Rudow, 1886 (Phygadeuon), Lectotype; syn. n. of Oresbius leucopsis (Gravenhorst, 1829) leucostictus Rudow, 1886 (Phygadeuon), syn. n. of Aptesis pugnax (Hartig, 1838) lycaenae Rudow, 1886 (Phygadeuon), Lectotype; syn. n. of Phygadeuon fumator Gravenhorst, 1829 nematorum Rudow, 1886 (Phygadeuon), Lectotype; syn. n. of Aptesis jejunatgor (Gravenhorst, 1807) pachycephalus Rudow, 1886 (Phygadeuon), syn. n. of Eristicus clarigator (Wesmael, 1844) pictipes Rudow, 1886 (Phygadeuon), Lectotype; syn. n. of Endasys parviventris (Gravenhorst, 1829) spinosus Rudow, 1886 (Phygadeuon), Lectotype; syn. n. of Apsilops cinctorius (Fabricius, 1775) amoena Rudow, 1881 (Pimpla), Lectotype; syn. n. of Perithous divinator (Rossi, 1790) castaniventris Kriechbaumer, 1894 (Pimpla), syn. n. of Itoplectis maculator cruentata (Rudow, 1883) colorata Rudow, 1883 (Pimpla), Lectotype; syn. n. of Zatypota albicoxa (Walker, 1874) ephippium Rudow, 1883 (Pimpla), syn. n. of Zaglyptus multicolor (Gravenhorst, 1829) flavipennis Rudow, 1883 (Pimpla), Lectotype now a synonym of Exeristes roborator (Fabricius, 1793) nematorum Rudow, 1881 (Pimpla), Lectotype now a synonym of Stilbops ruficorne (Gravenhorst, 1829) robusta Rudow, 1883 (Pimpla), Lectotype now a synonym of Exeristes roboratgor (Fabricius, 1793) rufipes Rudow, 1883 (Pimpla), Lectotype now a synonym of Apechthis compunctor (Linnaeus, 1758) melanosoma (Rudow, 1882) (Schreineria), Lectotype described as Cryptus melanosoma longicauda Rudow, 1886 (Stibeutes), syn. n. of Gelis rufithorax Horstmann, 1990; paeocc. in Gelis from Thomson, 1884 bispinosus (Rudow, 1886) (Sulcarius), Lectotype described as Phygadeuon bispinosus hesperophanis Picard, 1919 (Sycophrurus), syn. n. of Schreineria melanosoma (Rudow, 1882) analis Rudow, 1917 (Theroscopus), syn. n. of Aptesis nigrocincta (Gravenhorst, 1815) haemorhoidalis Rudow, 1914 (Theroscopus), syn. n. of Aptesis nigrocincta (Gravenhorst, 1815) collaris (Rudow, 1888) (Triptognathus), Lectotype described as Amblyteles collaris fumipennis (Rudow, 1888) (Triptognathus), Lectotype described as Amblyteles fumipennis tricolor Rudow, 1910 (Tryphon), Lectotype; syn. n. of Tryphon bidentatus Stephens, 1835